A Study on the Correlation Between Quality of Life and Unhealthy Emotion Among Patients With Endometriosis - He, Guimei; Chen, Jiebing; Peng, Zhangqing; Feng, Kai; Luo, Chunqi; Zeng, Xun (Frontiers in Psychology, 2022)
Objective: To investigate the influence of quality of life (QOL) on unhealthy emotions as well as relevant factors among the patients with endometriosis for supporting relevant clinical care. Methods: Through a convenient sampling method, a total of 139 patients with endometriosis were included for a questionnaire survey based on Hamilton Anxiety Scale (HAMA), Self-rating Depression Scale (SDS) and 12-item Short-Form (SF-12) for health survey. The results were analyzed. SPSS20.0 software was used for the statistical analysis on relevant data. If P < 0.05, there was statistical significance. Results: SF-12 for health survey covered two comprehensive indexes, i.e., physical component summary (PCS) and mental component summary (MCS) scores. MCS score was the main factor influencing anxiety and depression in patients with endometriosis. The higher the MCS score, the lower the anxiety and depression degrees in patients with endometriosis (OR=0.912, 95%CI: 0.877-0.949; OR=0.899, 95%CI: 0.866-0.933). PCS score was a factor influencing the anxiety degree. The higher the PCS score, the lower the anxiety degree (OR=0.936, 95%CI: 0.891-0.983). Conclusion: The QOL of patients with endometriosis is negatively correlated with anxiety and depression. Therefore, improvement in QOL may help relevant patient to relieve their unhealthy emotions.